Bone lesions in hairy cell leukemia: Diagnosis and treatment. (19th August 2020) - Robak, Pawel; Jesionek‐Kupnicka, Dorota; Kupnicki, Piotr; Polliack, Aaron; Robak, Tadeusz
Abstract: Skeletal involvement is a rare complication of hairy cell leukemia (HCL) with an incidence of approximately 3%. Bone lesions are commonly lytic, and the most common sites of involvement are the femoral head and neck. Skeletal involvement is typically associated with high tumor burden and bone marrow infiltration. However, isolated cases of skeletal disease without splenomegaly or bone marrow involvement are occasionally reported. This review focuses on skeletal lesions in HCL, particularly the pathogenesis, clinical symptoms, diagnostic methods, and treatment approach. A literature review of the MEDLINE database for articles in English concerning hairy cell leukemia, skeletal symptoms, bone involvement was conducted via PubMed. Publications from January 1970 to May 2020 were scrutinized. Additional relevant publications were obtained by reviewing the references from the chosen articles.